A Synthesis of Flexible Education Management Components - Srithep , Worapol; Vehachart, Rungchatchadaporn (Ratchaphruek Journal, 2026)
This study aims to synthesize the key components of flexible educational management through a documentary research approach and content analysis. The data were drawn from 18 research studies, academic articles, and relevant reports from both national and international sources. The selection criteria included publications produced between 2015 and 2025, studies directly addressing flexible educational management, works published in reputable academic journals or credible databases, and sources that have been cited in other scholarly publications. Data were analyzed using the Bar Chart Synthesis technique to determine the frequency and percentage of each identified component. The findings reveal six major components that are most widely recognized in the literature: 1) flexible policy and planning formulation, 2) flexible curriculum design, 3) diverse learning management, 4) flexible measurement and evaluation, 5) integration of technology and innovation, and 6) efficient resource management. These six components represent essential factors that support the adaptability of educational systems in responding to contemporary changes and challenges. The synthesized framework can serve as a guideline for educational institutions and related agencies in developing policies and practices aimed at enhancing flexible educational management.